Analisis Faktor-Faktor yang Mempengaruhi Organizational Citizenship Behavior pada Karyawan BPR di Batam - Jenetha Kartika; Evi Silvana Muchsinati (Universitas Kristen Maranatha, 2015)
The objective of this study is to examine the influence factor toorganizational citizenship behavior on BPR (Bank Perkreditan Rakyat)’s employees in Batam. The samples are employees of ten biggest BPR’s number of employees in Batam. Data collected by 389 questionnaire which deployed to 10 BPR. Structural Equation Model (SEM)-PLS (Partial Least Square) has been employed to analyze the data. The results of this study showed that 7 (seven) hypothesis are accepted and2 (two) the hypothesis are rejected. Four independent variables (employee development, employee communication, rewards and recognition and leadership) have a significant positive effect on employee engagement, employee engagement asintervening variables has a significant positive effect on organizational citizenship behavior then two independent variables (employee communication and reward andrecognition) have a positive significant effect on the dependent variable organizational citizenship behavior by mediating role of employee engagement while the other two independent variables (employee development and leadership)had no significant effect on organizational citizenship behavior by mediating role of employee engagement.Keywords: Employee Development, Employee Communication, Reward and Recognition, Leadership, Employee Engagement, Organizational Citizenship Behavior, Structural Equation Model (SEM), Partial Least Square (PLS).